The importance of accurate site location for skinfold measurement - Hume, P.; Marfell-Jones, M. (Journal of Sports Sciences, 2008)
We assessed the importance of accurate site location for skinfold measurement in ten healthy males in a cross-sectional quantitative study. Nine measurements, in a 1-cm grid pattern, centred on each of eight ISAK-specified skinfold sites, were taken three times at each grid point by each of two ISAK Level 4 practitioners using Harpenden skinfold callipers. The presence of significant systematic discrepancy between reliability measures of different skinfold sites and grid points for each of the two testers was determined using P-values. Effect sizes were calculated to show the magnitude of effects. Skinfolds taken at the eight peripheral grid points were generally different from the skinfolds taken at a central ISAK grid point and there was an effect by direction away from the central ISAK point (anterior, posterior, superior or inferior). The subscapular skinfold had the least number of differences (three) and the abdominal had the most (eight). All other skinfold sites showed some variation with most care needed in marking the biceps and triceps skinfold sites. Adherence to identifying, marking, and measuring at the defined site is essential.